1986
DOI: 10.1002/bit.260280412
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of the maximum specific growth and fermentation rate of Zymomonas mobilis by ethanol

Abstract: The inhibition of the maximum specific growth and fermentation rate of Zymomonas mobilis by ethanol was studied in turbidostat cultures at constant and stepwise changed ethanol concentrations. Up to 50 g/L ethanol, the inhibition kinetics can be approximated by a linear relationship between the specific growth rate and the ethanol concentration. Above this level, deviations from this linearity are observed. The specific fermentation rates were less inhibited by ethanol than was the specific growth rate. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…A difference between the inhibitory effect of added and produced ethanol, in conjunction with different intracellular and extracellular ethanol concentrations, was proposed for yeast in studies prior to 1983 (34,479,497). However, subsequent unrebutted work has discounted this hypothesis for yeast (133,134,135,229,395), Z. mobilis (313), and E. coli (168). In light of these data and in particular biophysical analyses indicating that substantial differences between intracellular and extracellular ethanol concentrations across plasma membranes can exist for at most short periods (313,395), it would appear unlikely that this discrepancy is due to a difference in the inhibitory effect of added and produced ethanol.…”
Section: Native Cellulolytic Strategymentioning
confidence: 99%
“…A difference between the inhibitory effect of added and produced ethanol, in conjunction with different intracellular and extracellular ethanol concentrations, was proposed for yeast in studies prior to 1983 (34,479,497). However, subsequent unrebutted work has discounted this hypothesis for yeast (133,134,135,229,395), Z. mobilis (313), and E. coli (168). In light of these data and in particular biophysical analyses indicating that substantial differences between intracellular and extracellular ethanol concentrations across plasma membranes can exist for at most short periods (313,395), it would appear unlikely that this discrepancy is due to a difference in the inhibitory effect of added and produced ethanol.…”
Section: Native Cellulolytic Strategymentioning
confidence: 99%
“…To accurately describe the formation rate of the key component at low ethanol concentrations and under substrate-limited conditions, the formation rate expression for the key component [34,35] is a function of substrate concentration, given by:…”
Section: Bioethanol Manufacturing Process Modelmentioning
confidence: 99%
“…However, typical models consider only the kinetic expressions of fermentation for constant temperature conditions. The proposed mathematical model here takes into consideration the temperature effect on kinetics parameters, mass and heat transfer, in addition to the kinetic equations modified from the indirect inhibition structural model developed in the literature [34,35].…”
Section: Bioethanol Manufacturing Process Modelmentioning
confidence: 99%
“…It has previously been shown that a FBF for ethanol production from glucose by naturally immobilized Zymomonas mobilis could be operated with D > 11μ max [10]. Because the volumetric productivity (r p ) of this system was about 10-times higher than μ max at the ethanol concentration being produced [11], this is evidence that there was a low degree of diffusional limitation within the Zymomonas biofilm. In contrast, experimental work with flocculent yeast in a diffusion cell has shown that the rate of glucose diffusion was only 17% compared to the rate in pure water [12].…”
Section: Introductionmentioning
confidence: 87%